THE CATECHIST / RELIGION TEACHER-TARGETED ABILITIES AND COMPETENCES - VASILE TIMIȘ (Studia Universitatis Babes-Bolyai, 2014)
ABSTRACT. Knowing ones religious values represent a form of cultural security, a sign of civic and culturally attitudes. Religious education invites to reflection, to self-knowledge, to a conversion to the world of values, having the purpose of bringing communion between people and solidarity between the members of a community. Recent years have proven that the catechetical activity of the Church and the presence of religion in schools are necessary not only for religious denominations, but also for the Romanian society as a whole, which, by these rightful measures gained access to its own spirituality and to an essential tool in teaching the young. In Romanian space, Christian belief has acted as a unifying and perpetuating factor for the nation. Being religiously initiated means to be educated, means to have the capacity to increase and to support the education. Religious realities of contemporary Romania show that the role of the religion teacher is a very important one. Given the oversizing of the urban parish, the teacher manages constantly the religious education of the young. This quasi-sacerdotal function of the religion teacher imposes certain requirements in the training of the teacher himself, in his continuous self-evaluations and self-improvement.